Competence through authenticity – open data in education - Veteli, Peitsa; Lassila-Perini, Kati (Journal of physics. Conference series, 2024)
The modern world is a very data-driven place, bristling with repositories of openly available information, yet these resources are seldom used in education below university levels. This may partially be due to lack of sufficient teacher training and ongoing support structures, but also due to lack of information on useful methods. We present the case for secondary school level use of open, authentic real world data and easily accessible programming as cross-disciplinary tools for advancing the students’ scientific literacy and broader subject knowledge. The use of computational essays and interactive programming exercises promotes modern ways of knowledge creation and allows the students to participate in doing science as practising scientists and industry workers would. Feedback from teacher trainings, student workshops and school courses between 2016-2022 indicates a very positive reception with topics ranging widely from analysis of particle physics data from the CMS experiment at CERN to climate questions or sociological problems.